Environmental risk and growth in foreign direct investment: Is the composition of FDI in sub-Saharan Africa a speculative type? - Williams Ohemeng; Kenneth Ofori-Boateng; Elvis Kwame Agyapong; Joseph Darmoe (Cogent Economics & Finance, 2023)
The study explores the influence of environmental risk (macroeconomic uncertainty and environmental sustainability risk) on the inflow of foreign direct investment (FDI), utilizing data from 37 economies in sub-Saharan Africa (SSA) from 1996 to 2019. The empirical analyses were carried out using Panel Corrected Standard Error (PCSE) estimation technique. The outcomes show that higher level of uncertainty in GDP growth, inflation uncertainty and financial development volatility induce more FDI inflows whilst uncertainty in exchange rate adversely impacts FDI inflows in SSA. The paper highlights how effectiveness of governance, stable political atmosphere and quality of regulatory structures moderate the relationship between environmental risk and FDI with striking varying outcomes. Consistent with the pollution haven hypothesis, the interactions between governance effectiveness, political stability, regulatory structures and environmental risk suggest that the sub-region is attracted to risk loving speculative investors who prefer poorly regulated and weak governance environment. From policy implication, the findings imply that FDI composition in the sub-region may have moved more towards the speculative type, which may not necessarily be classified as pro-growth in nature.
Keywords: F14; F18; F21; F23; F62; 330; environmental sustainability risk; foreign direct investment; macroeconomic risk; panel corrected standard errors; Sub-Saharan Africa